ANALISIS PENGARUH PENDAPATAN MARGIN MURABAHAH DAN PENDAPATAN BAGI HASIL MUSYARAKAH TERHADAP LABA BERSIH PT BANK NEGARA INDONESIA SYARIAH (Periode Tahun 2012 – 2018) - Herry Winarto; Eva Nuraisyah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This type of research uses quantitative research. The data source used in this study is secondary data. Data analysis method used is hypothesis testing, namely the t test and f test. The results of this study indicate that Murabahak Margin Income and Musyarakah Profit Sharing Revenue simultaneously have a significant effect on Net Profit of Murabahak Margin Income partially, and Musyarakah Revenue Sharing has a significant influence, PT Bank Negara Indonesia Tbk. To obtain data, researchers used the website of PT Bank Negara Indonesia Tbk, and the Indonesia Stock Exchange (IDX). By conducting research on financial data for the period 2012-2018 analyzed using SPSS 25.0